2019
DOI: 10.37358/rc.19.6.7262
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antimicrobial Assessment of Some New 2-(Thiazol-5-yl)-1,3,4-oxadiazoles

Abstract: Considering the promising antimicrobial activity of compounds bearing the thiazole or the oxadiazole rings in their structures, we set out to obtain new antimicrobial molecules bearing the 2-(thiazol-5-yl)-1,3,4-oxadiazole schaffold. The structures of the 8 new compounds obtained was confirmed by physicochemical characterization including: 1H-NMR, MS and elemental analysis. Antimicrobial activity was investigated against 5 Gram-positive bacterial strains, 2 Gram-negative bacterial strains and 2 fungal strains.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The results revealed that compounds (17)(18) exhibited better antibacterial activity than standard drug Ampicillin except against E. coli (Table 9). In case of antifungal activity compounds (17)(18) showed reduced activity as compared to standard drug Miconazole ( 12) [55]. 13).…”
Section: Antibacterial and Antifungal Activities Of 25-disubstituted-...mentioning
confidence: 99%
See 1 more Smart Citation
“…The results revealed that compounds (17)(18) exhibited better antibacterial activity than standard drug Ampicillin except against E. coli (Table 9). In case of antifungal activity compounds (17)(18) showed reduced activity as compared to standard drug Miconazole ( 12) [55]. 13).…”
Section: Antibacterial and Antifungal Activities Of 25-disubstituted-...mentioning
confidence: 99%
“…Compound 55 found to be most active (ZOI = 69.5-80.5 mm) against most of the tested fungal strains among synthesized derivatives (Table24). Overall active compounds(54)(55)(56) showed excellent activity as compared to standard drugs Clotrimazole and Ciprofloxacin (Table23, 24)[66]. S. aureus, E. coli and P. aeruginosa (MIC range = 12.5-25 µg/mL) except 57 against E. coli (MIC = 50 µg/mL)…”
mentioning
confidence: 99%